Geomorphometry as a tool to Estimate Volume and Distribution of Coralligenous Habitats Along the Apulian Continental Shelf. - Marchese F.; Savini A.; Bracchi V. A.; Corselli C. (2017)
Coralligenous bioconstructions represent an outstanding example of calcareous build-ups of biogenic origin of the Mediterranean Sea. They provide sensitive and vulnerable habitats actually included in the list of endangered habitats by governmental organizations and conservation agencies (e.g. OSPAR; red list habitats). They are especially sensitive to the ongoing global change (i.e. ocean acidification) that can produces a negative impact on the calcification of the organisms’ skeleton of which they are formed (mainly calcareous algae and invertebrates). The extent to which the coralligenous bioconstructions can modify the submarine environment, affecting the evolution of submerged landforms is extremely variable. Within the framework of the BIOMaP Project (BIOcostruzioni Marine in Puglia, - P.O. FESR 2007/2013), promoted by Puglia region, Italy, new high resolution acoustic data were acquired in order to identify and locate Coralligenous Habitats along the Apulian continental shelf (South Adriatic Sea – Northern Ionian Sea), from 10 down to 100 meters of water depth, in 21 Site of Community Interest and 3 Marine Protected Areas. The dataset covered an area of 1000 km2 and was obtained through the use of MultiBeam Echosounder Systems and Side Scan Sonars. Ground-truthing were collected by 3 ROV dives (Prometeo ROV) and more than 30 underwater camera transects. The present study is based on a new experimental methodology designed to analyze multibeam data by means of geomorphometric analyisis in order to (1) figure out relationships between the observed morphologies and the associated distribution and (2) quantify the total volume of selected Coralligenous build-ups. Our work underlines the importance of combining acoustic survey techniques and geomorphometric analysis in order to offer quantitative information for a new understanding of the importance of Coralligenous Habitat as carbonate deposits of the Mediterranean shelf